Optimizing Surau as an Education Center in the Pandemic Period: (Community-Based Research) - Rozaanah Rozaanah; Muhammad Iqbal; Fakhrurrozi Fakhrurrozi; Ade Muhammad Ritonga; Ahmad Afandi (ASSUNNAH PRESS, 2022)
Community service activities are a community service activity that is needed by students to hone student skills and personalities so that they can go directly to the community. Therefore the KKL conducted by STAI AS-SUNNAH students aims so that all elements of society can participate in this activity by